Origanum Sipyleum Methanol Extract in Combination with Ponatinib Shows Synergistic anti-Leukemic Activities on Chronic Myeloid Leukemia Cells. (26th November 2022) - Kayabasi, Cagla; Yilmaz Susluer, Sunde; Balci Okcanoglu, Tugce; Ozmen Yelken, Besra; Mutlu, Zeynep; Goker Bagca, Bakiye; Caliskan Kurt, Cansu; Saydam, Guray; Durmuskahya, Cenk; Kayalar, Husniye; Ozbilgin, Ahmet; Biray Avci, Cigir; et al.
Abstract: Origanum sipyleum is used in folk medicine due to its anti-inflammatory, antimicrobial, and antioxidant properties. Ponatinib, an effective tyrosine kinase inhibitor in the treatment of chronic myeloid leukemia (CML), has severe side effects. Thus, we aimed to determine a novel herbal combination therapy that might not only increase the anti-leukemic efficacy but also reduce the dose of ponatinib in targeting CML cells. Origanum sipyleum was extracted with methanol (OSM), and secondary metabolites were determined by phytochemical screening tests. The cytotoxic effects of OSM on K562 cells were measured by WST-1 assay. Median-effect equation was used to analyze the combination of ponatinib and OSM (p-OSM). Apoptosis, proliferation, and cell-cycle were investigated by flow-cytometry. Cell-cycle-related gene expressions were evaluated by qRT-PCR. OSM that contains terpenoids, flavonoids, tannins, and anthracenes exhibited cytotoxic effects on K562 cells. The median-effect of p-OSM was found as synergistic; OSM reduced the ponatinib dose ∼5-fold. p-OSM elevated the apoptotic and anti-proliferative activity of ponatinib. Consistently, p-OSM blocked cell-cycle progression in G0 /G1, S phases accompanied by regulations in TGFB2, ATR, PP2A, p18, CCND1, CCND2, and CCNA1 expressions. OSM enhanced the anti-leukemic activity of ponatinib synergistically via inducing apoptosis, suppressing proliferation, and cell-cycle. As a result, OSM might offer a potential strategy for treating patients with CML.